Effectiveness of Music Therapy as an Intervention in Patients with Hypertension: A Literature Review - Odis Runesi; Sukihananto (LPPM STIKES Al-Ma'arif Baturaja, 2024)
Hypertension is a medical condition often associated with high blood pressure, and if not properly managed can increase the risk of heart disease and stroke. Although pharmacological treatment has become the standard in managing hypertension, non-pharmacological therapies such as music therapy can be used as a non-pharmacological approach that has the potential to strengthen the management of this disease. This study aims to determine the effectiveness of music therapy as an intervention in hypertensive patients. The conceptual framework used is by collecting some literature that discusses the same topic by looking at research abstracts. There are 3 database sources used to search for literature, namely Proquest, Science Direct, clinicallkey and Wiley journals. Music therapy is one of the alternative therapies or non-pharmacological therapies that can be used as hypertension therapy. This music therapy can be a guideline and recommendation for nurses to apply to patients with hypertension, besides that, people with hypertension can use music therapy independently.